Budaya Organisasi dalam Mendukung Merdeka Belajar-Kampus Merdeka - Meita Istianda; Steven Anthony (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2022)
Merdeka Belajar-Kampus Merdeka, including political policies, which are relevant to the development of the Industrial Revolution 4.0 era. This political policy can also answer the problem of the impact of the Covid 19 pandemic on the teaching and learning process in higher education. The political policy of Merdeka belajar-Kampus Merdeka will determine the direction of the future development of Indonesian education. For this political policy to be accepted, it must be supported by an adaptive organizational culture. This research discusses the political policy of Merdeka belajarKampuss Merdeka, and the organizational culture that universities must prepare to support these political policies. This research is qualitative research. Retrieval of data, through literature study. The results of the research show that the political policy of Merdeka Belajar-Kampuss Merdeka is predicted not to be followed by an adaptive organizational culture in support of Merdeka belajaKampusus Merdeka.